Clinical, microbiological, and immunological evaluation of patients in corrective orthodontic treatment - Mariana Umekita Shirozaki; Raquel Assed Bezerra da Silva; Fábio Lourenço Romano; Léa Assed Bezerra da Silva; Andiara De Rossi; Marília Pacífico Lucisano; Michel Reis Messora; Magda Feres; Arthur Belém Novaes Júnior (SpringerOpen, 2020)
Abstract Background The objective was to analyze clinical, microbiological, and immunological periodontal parameters in patients in corrective orthodontic treatment. Materials and methods Twenty-eight patients were selected. Plaque index (PI), bleeding on probing (BOP), width of keratinized gingiva, levels of 40 bacterial species, and of 3 cytokines (IL-1β, MMP-8, and TNF-α) in gingival crevicular fluid (GCF) were evaluated at T0, before orthodontic treatment; T1, 6 months; and T2, 12 months post-treatment. Non-parametric, Friedman, Wilcoxon, ANOVA, and Spearman correlation coefficient tests were used for statistical analyses, with the significance level of 5%. Results No significant difference was found for the width of keratinized gingiva, but PI presented a significant increase at T1 and T2 (p < 0.05) when compared with T0. The percentage of sites with BOP increased significantly from T0 to T1 (p < 0.05); however, at T2, the values decreased and did not differ anymore from T0 (p > 0.05). In the microbiological analysis, red complex pathogens were in significantly greater proportions in T2 compared with T0 (p < 0.05). There was no statistically significant difference in the cytokine levels between the periods but there was a positive correlation between BOP and IL-1β (r = 0.49 p = .01) and TNF-α (r = 0.39 and p = .05). Conclusion In conclusion, corrective orthodontic treatment caused clinical periodontal alterations regarding biofilm accumulation and gingival bleeding, with alteration of periodontopathogens.